Why a Law of Cure, Its Necessity for Diseases to Cure them for the Waiting World? When? and How? (Advancements in Homeopathic Research, 2022)
How diseases in human beings, in animals and even in vegetable plants have started on this Planet (Earth). Does anybody know? Why these diseases and what were/are the causes of them? How to treat these diseases for survival? Was there any rule, method or Law to treat various types of diseases in humans, animals and plants? Was lives of humans, animals, and plants were short or long (days, months, years)? We all die at a certain age and time with causes or without any cause. Then, what are the causes? Why we, humans die? We say that there is a Soul in the body, if so what? Has anybody seen the Soul? Where in the body the Soul resides? How long maximum periods the human body can survive or live? Anybody knows? When the time comes all departs (die). Why? Is it so that what is “BORN HAS TO DIE”? How and why question arises? Is death, a departure from this Planet? Is there any rebirth or Incarnation after death? Belief is there that “SOUL” lives after death? Where? Is there HEAVEN and HELL? Who are the people who go to HEAVEN OR HELL? Is there any other world for the dead people? Is it not all a mystery? Who has created this World with so many planets with a BIG DOME to which we call blue SKY? We have days and nights. In days we have brightness, we call it light (daytime) so that we can see each other, read books, newspapers, work, etc. What or which object gives brightness or light to us? We call it SUN, a big round lamp in the sky. It is millions of miles/kilometers away from our Planet. How is it so to give so much light to the whole Earth? Does it require a lot of coals or woods? It also produces energy or heat for survival of humans, animals, and plants. What about the nights? It is so arranged that for 15 days we get some light by which we can see each other but we cannot read books or newspapers, but can do some work etc. and to that object we call it MOON. How is it? Why only 15 days? What about other days? Darkness, it is a sleeping time. It is very good time for thieves. This period we call nights then slowly we entered into modern era (with candle lights, oil, lamps and electricity). Who has done or created ALL? We call him GOD. But there are people who do not believe HIM as GOD and we call them Atheists as they have not seen HIM. Others who believe HIM they experience HIM by prayers and certain rituals
Keywords: humans; animals; plants